Vitamin T : Threads & Textiles in Contemporary Art. - Porter, Jenelle (London : Phaidon Press Limited, 2019)
Achaintre, Caroline ; Adams, Igshaan ; Aladaǧ, Nevin ; de Amaral, Olga ; Amer, Ghada ; Anatsui, El ; Antufiev, Evgeny ; Antunes, Leonor ; Apfelbaum, Polly ; Arnardóttir, Hrafnhildur ; Shoplifter ; Lemos Auad, Tonico ; Auberbach, Lisa Anne ; Baldock, Jonathan ; Barlow, Phyllida ; Barrada, Yto ; Beasley, Kevin ; (etc.)
The bestselling and acclaimed survey of more than 100 global artists, chosen by an international panel of experts for their work with threads, stitching, and textiles Celebrating tapestry, embroidery, stitching, textiles, knitting, and knotting as used by visual artists worldwide, leading curators, critics, and art professionals have nominated more than 100 global living artists for inclusion in this stunning and wide-ranging survey. As boundaries between art and craft have blurred, artists have increasingly embraced these materials and methods, with the resulting works being coveted by collectors and exhibited in museums worldwide. A vital handbook for collectors and contemporary-art followers, this acclaimed and ground-breaking survey is a vibrant and incredibly timely survey. (provided by publisher)
boek